KONSTRUKSI MODEL HUBUNGAN DUA VARIABEL DENGAN ANALISIS REGRESI SPLINE - Yozza, Hazmira; Afrimayani, Afrimayani (IAIN Batusangkar, 2019)
This paper discussed about the construction of a model the relationship between a dependent variabel and a independent variabel using spline analysis regression. This methods is usually used when the relationship between variables is unknown. This methods is applied to construct the growth curve for children under 3 years of age in Padang.